It's got to be perfect? Differentiating the unique daily relationships of perfectionism and excellencism with employee effort, performance and fatigue - Monique Mohr; Carolin Dietz (Journal of Occupational and Organizational Psychology, 2025)
Employees are increasingly striving for perfection at work. Commonly deemed to be associated with more advantages than disadvantages for employees and organizations, this perfectionism is oftentimes societally and organizationally demanded, appreciated or rewarded. To date, however, research findings on this topic are inconclusive. Taking new theoretical developments in perfectionism research into account, we propose that the current view that perfectionism is an adaptive pursuit at work is probably distorted. Building on the recently developed Model of Excellencism and Perfectionism and using a daily diary design ( N 0.167em=0.167em127 participants providing n 0.167em=0.167em10180.167emdays of data), we examined how excellencism and perfectionism relate to employee effort, performance and well-being in daily work. As expected, results of multilevel path modelling showed that daily excellencism relates positively to both effort intensity and persistence and, via effort, to in-role performance. Unexpectedly, effort and, thus, excellencism, were unrelated to fatigue. Daily perfectionism did not show unique relationships over and above the respective relationships of daily excellencism. Accordingly, contrasted with excellencism, perfectionism seems to be an unneeded pursuit at work. As we discuss, the findings of our study are of both theoretical and practical criticality.
Keywords: 650; effort; excellencism; goals; perfectionism